Students Perception of Factors Contributing to Depression During The Covid-19 Pandemic - Mohd Nor, Muhammad Helmi; Ariffin, Arihasnida (Research and Innovation in Technical and Vocational Education and Training, 2022)
The purpose of study is to identify the students’ perception towards factor of family, environment, and social contributing to depression during Covid-19 pandemic to students of the Faculty of Technical and Vocational Education in Universiti Tun Hussein Onn Malaysia. This study involves 301 sample consisting of students from year 1 to year 4 in the Bachelor of Vocational Education (ISMPV) in program General Machining, Building Construction, Catering, Welding and Metal Fabrication, Electrical and Electronics, Multimedia and Creative, and Refrigeration and Air Conditioning. The simple random sampling method is used based on the study procedure from the selected population group and has homogeneous population characteristics that have the same characteristics in this study. Set of questionnaires has been distributed to collect data in the medium of google forms which contains four sections where Section A (demographics), Section B (perceptions of family factors), Section C (perceptions of environmental factors) and Section D (perceptions of social factors) as a research instrument. The data were collected, analyzed using Statistical Package for Social Sciences for Windows Version 25 (SPSS) software descriptively such as mean scores and standard deviations. The findings of the study showed that the main factors causing depression during the Covid-19 pandemic among students were social factors (mean 3.48), followed by environment factors (mean 3.34) and family factors (mean 2.87). The findings of this study also show that students’ perceptions of the three factors that cause depression are at a moderate level. This study can help the university to identify students that suffer from depression and can be overcome immediately.